Os bastidores da queixa escolar: da sala de aula ao consultório psicológico - Rosa, Anyellem Pereira (2011)
The great number of children with school issues referred to public and private clinical psychologists is a fact that requires consideration for two aspects: first, the school stigmatizes the child and his/her family without actually helping them and, secondly, psychological care demands of the professional knowledge and concepts that cover the whole complexity of such issues. Given this context, this study aims to contribute for a better understanding of the school issues following the paths they travel from school to psychological care, and discuss the concepts and practices present, enabling a deeper reflection on aspects such as maintenance of issues as well as overcoming them and their effects on the lives of the individuals. Considering that the complaints come from the school, this study began investigating this universe. We selected two public and two private educational institutions and we interviewed, respectively, the directors and coordinators. A total of five interviews were conducted. We then requested these professionals to indicate one or two psychologists who they tend to refer children with school problems. Thus, two psychologists were interviewed; one indicated by a private school and the other, a health service psychologist mentioned by the public schools. Analysis of the interviews showed that the scenes of school issues are made up by the roles occupied by all those involved in the network of relationships in which the issue is constructed (teachers, family and child psychologist), by what is thought of the child, by the human developmental and educational concepts, by the concrete conditions of educational work and training of educators and psychologists. These aspects were discussed and related to other topics, and grouped in three main areas: 1) the role of schools highlighting the specificity of education, teacher working conditions, the relation between family / school / society; 2) concepts of school issues focusing on blaming the child and the dichotomy between the cognitive and affective dimension of the individual and 3) the training and work of the psychologist who receives the child with the issue discussing the scenes of school issues outside the school walls, specifically in psychology practices, and analyzing the views of the psychologists interviewed regarding school issues, the specificity of the work of the psychologist. This research revealed the urgent need to disclose actions in psychology that seek to understand and overcome the problems identified in school life, practices which are not allies with the reductionist way of conceiving school issues and that the institution can intervene before there is a wrong referral, to be resolved outside the school walls.